PENGARUH PARTISIPASI MASYARAKAT DAN TRANSPARANSI KEBIJAKAN TERHADAP PENGAWASAN ANGGARAN DANA DESA DI KECAMATAN DELIMA KABUPATEN PIDIE - Maisur Ramzijah (Jurnal Sains Riset, 2020)
This research is aimed to test the effect of the society participation and policy transparency of monitoring of the village fund budget. The variable used in this study is the application of accounting information systems. samples in this study with total of 100. Technique of sampling is applied with random sampling. The analysis method use multiple linear regression. The results of research show that the society participation and policy transparency have significant effect on monitoring of the village fund budget. Keywords : society participation,policy transparency, monitoring of the village fund budget.